Os saberes profissionais das coordenadoras pedagógicas da educação infantil: uma análise dos registros no âmbito de um processo formativo em uma rede do interior paulista - Ragonha, Eliani (Universidade Federal de São Carlos, 2025)
This study argues for the importance of investing in teachers professional development and in strengthening the qualified training role of pedagogical coordinators, as well as their contribution to reflecting on and improving the quality of training processes in early childhood education schools and systems in our country. In this sense, our focus is on investigating the continuing education of a group of pedagogical coordinators at this stage of basic education, through the description of processes and the analysis of documentary records of the actions carried out, aiming to understand the professional knowledge produced in this process. The guiding question of the study seeks to understand which forms of professional knowledge are produced in the continuing education of pedagogical coordinators in early childhood education, oriented toward the reflective process of professional practice. To develop the study, we adopted a descriptive method, based on a documentary research methodology with a qualitative approach, using as instruments the analysis of public data and personal records related to continuing education meetings conducted with pedagogical coordinators in early childhood education in 2016, within a municipal school system in the interior of the state of São Paulo. The theoretical framework was grounded in authors from the epistemology of practice, such as Tardif (2022), Schön (1997), Nóvoa (2023), Alarcão (1996, 2005), and Imbernón (2016). The analyses were organized into thematic axes derived from the study objectives and research question. The results reveal that the central axis of continuing education programs should be reflection on the practice of the professionals involved, aiming at improving teachers’ practices and fostering the autonomous thinking of participants. Within this process, beyond the knowledge constructed through continuing education, the identity of the early childhood education pedagogical coordinator was collectively shaped. Some gaps were also identified: the use of the same content and methodologies for coordinators across all schools, without considering different contexts of practice; the need to be present in schools alongside coordinators, discussing their challenges in situ; the necessity of developing a municipal curricular document; and the absence of continuing education initiatives carried out by the municipality in direct partnership with universities.
The professional knowledge base of pedagogical coordinators in early childhood education: a study of records within a professional development process in a regional school network of São Paulo
Keywords: Educação Infantil; Coordenação Pedagógica; Formação Continuada; Saberes Profissionais; Registros Documentais; CIENCIAS HUMANAS::EDUCACAO; 4. Educação de Qualidade